Communicating construction : insight, experience and best practice - Male, Liz; Norton, Penny, 1973-; McCapra, Alastair (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is a wide-ranging exploration of PR and communication in the construction industry, with a strong emphasis on communications theory, strategy and technique"--
Communications for planning / Penny Norton -- Communications for architecture / Dan Gerrella -- Communications for major contractors / Andrew Geldard.
OCLC-licensed vendor bibliographic record.
Keywords: Construction industry -- Communication systems; Construction industry -- Public relations; ARCHITECTURE / Professional Practice; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Customer Service